Muscle strength adaptation between high-load resistance training versus low-load blood flow restriction training with different cuff pressure characteristics: a systematic review and meta-analysis - Chang, Hualong; Yan, Jing; Lu, Guiwei; Chen, Biao; Zhang, Jianli (Frontiers in Physiology, 2023)
Purpose: In this systematic review and meta-analysis, blood flow restriction (BFR) with low-load resistance training (BFR-RT) was compared with high-load resistance training (HL-RT) on muscle strength in healthy adults. The characteristics of cuff pressure suitable for muscle strength gain were also investigated by analyzing the effects of applying different occlusion pressure prescriptions and cuff inflation patterns on muscle strength gain.Methods: Literature search was conducted using PubMed, Ovid Medline, ProQuest, Cochrane Library, Embase, and Scopus databases to identify literature published until May 2023. Studies reporting the effects of BFR-RT interventions on muscle strength gain were compared with those of HL-RT. The risk of bias in the included trials was assessed using the Cochrane tool, followed by a meta-analysis to calculate the combined effect. Subgroup analysis was performed to explore the beneficial variables.Results: Nineteen articles (42 outcomes), with a total of 458 healthy adults, were included in the meta-analysis. The combined effect showed higher muscle strength gain with HL-RT than with BFR-RT (p=0.03, SMD=−0.16, 95% CI: −0.30 to −0.01). The results of the subgroup analysis showed that the BFR-RT applied with incremental and individualized pressure achieved muscle strength gain similar to the HL-RT (p=0.8, SMD=−0.05, 95% CI: −0.44 to 0.34; p=0.68, SMD=−0.04, 95% CI: −0.23 to 0.15), but muscle strength gain obtained via BFR-RT applied with absolute pressure was lower than that of HL-RT (p< 0.01, SMD=−0.45, 95% CI: −0.71 to −0.19). Furthermore, muscle strength gain obtained by BFR-RT applied with intermittent pressure was similar to that obtained by HL-RT (p=0.88, SMD= −0.02, 95% CI: −0.27 to 0.23), but muscle strength gain for BFR-RT applied with continuous pressure showed a less prominent increase than that for HL-RT (p<0.05, SMD=−0.3, 95% CI: −0.48 to −0.11).In general, HL-RT produces superior muscle strength gains than BFR-RT. However, the application of individualized, incremental, and intermittent pressure exercise protocols in BFR-This is a provisional file, not the final typeset article RT elicits comparable muscle strength gains to HL-RT. Our findings indicate that cuff pressure characteristics play a significant role in establishing a BFR-RT intervention program for enhancing muscle strength in healthy adults.